SERVICE INDUSTRIES INNOVATIVE DEVELOPMENT AS A BASIS FOR RUSSIAN SERVICE ECONOMY DEVELOPMENT - Irina А. DUDAKOVA; Yulia V. GLADKOVA (Advanced Engineering Research, 2010)
The problem of macro-economic importance of service industries and service economy development, as well as economic trends of service industries development in RF, and their dynamic growth factors  are analysed. The Russian service practice innovations are featured.